(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the development of technology for producing acetylene alcohols, aromatic diol, and their vinyl esters. As well as butin-2-diol-1,4 based on acetylene; The vinylation of 3,6-dimethyloctin-4-diol-3,6 and resorcinol with acetylene was studied at atmospheric pressure in the presence of two- and three-component high-base systems; the nature of the catalysts, the effect of solvents, and the temperature were determined.